The determinants of non-performing loan in Malaysia / Shahira Puteri Shaari - Shaari, Shahira Puteri (Faculty of Business and Management, 2017)
This study examines the relationships between non-performing loan (NPL) and the determinants of exchange rate (ER), inflation rate (IR) and lending interest rate (BLR) from the quarter 4 of year of 2005 to quarter 2 of year 2017 which base on quarterly data. The data was analyzed by using Autoregressive Distributed Lag (ARDL) in order to define the statistical relationship among the variables. Besides, there are steps involved in the study begin with Autoregressive Distributed Lag (ARDL) methods and proceed with Descriptive Analysis, Diagnostic Checking, Unit Root tests, and Long Run Form. In Diagnostic Checking, some tests done to check the significant presents of autocorrelation, heteroscedasticity, the normality of data distribution and model specification. The result of this study shows that there is a significant relationship between the Non-performing loan (NPL) and the exchange rate (ER) and inflation rate (IR), while lending interest rate did not have any relationship with the NPL. As conclusion this studies has shows that the ER, IR and BLR become the factors that affecting the NPL ratio in Malaysia.